Zoonotic Malaria – Global Overview and Research and Policy Needs - Ramasamy, Ranjan (Frontiers in Public Health, 2014)
The four main Plasmodium species that cause human malaria, Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, and Plasmodium ovale, are transmitted between humans by mosquito vectors belonging to the genus Anopheles. It has recently become evident that Plasmodium knowlesi, a parasite that typically infects forest macaque monkeys, can be transmitted by anophelines to cause malaria in humans in Southeast Asia. Plasmodium knowlesi infections are frequently misdiagnosed microscopically as P. malariae. Direct human to human transmission of P. knowlesi by anophelines has not yet been established to occur in nature. Knowlesi malaria must therefore be presently considered a zoonotic disease. Polymerase chain reaction is now the definitive method for differentiating P. knowlesi from P. malariae and other human malaria parasites. The origin of P. falciparum and P. vivax in African apes are examples of ancient zoonoses that may be continuing at the present time with at least P. vivax, and possibly P. malariae and P. ovale. Other non-human primate malaria species, e.g., Plasmodium cynomolgi in Southeast Asia and Plasmodium brasilianum and Plasmodium simium in South America, can be transmitted to humans by mosquito vectors further emphasizing the potential for continuing zoonoses. The potential for zoonosis is influenced by human habitation and behavior as well as the adaptive capabilities of parasites and vectors. There is insufficient knowledge of the bionomics of Anopheles vector populations relevant to the cross-species transfer of malaria parasites and the real extent of malaria zoonoses. Appropriate strategies, based on more research, need to be developed for the prevention, diagnosis, and treatment of zoonotic malaria.